The limits of the self immunology and biological identity - Pradeu, Thomas (Oxford : Oxford University Press, 2012)
Immunology asserts that an individual can be defined through self and nonself. Thomas Pradeu argues that this theory is inadequate, because immune responses to self constituents and immune tolerance of foreign entities are the rule, not the exception.
Description based on online resource; title from PDF title page (viewed on Apr. 19, 2012).
Includes bibliographical references and index.
Keywords: Immune system; Immunology -- Philosophy; Self (Philosophy)